Beetles of Eastern North America - Evans, Arthur V.; Princeton University Press (Princeton : Princeton University Press, 2014)
A comprehensive full-color guide to the remarkably diverse and beautiful beetles of the United States and Canada east of the Mississippi River. It is the first color-illustrated guide to cover 1,406 species in all 115 families that occur in the region - and the first new in-depth guide to the region in more that forty years. Lavishly illustrated with over 1,500 stunning color images by some of the best insect photographers in North America, the book features an engaging and authoritative text by noted beetle expert Arthur Evans.
Introduction to beetles : Beetle anatomy Behavior and natural history When and where to find beetles Observing and photographing beetles Beetle conservation and the ethics of collecting Collecting and preserving beetles Making a beetle collection Keeping and rearing beetles in captivity Taking an active role in beetle research --Illustrated key to the common beetle families of eastern North America --Appendix: Classification of the beetles covered in this book.
Includes bibliographical references (pages 527-529) and index.
Keywords: Beetles -- North America -- Identification